The Use of Collision Detection to Infer Multi-Camera Calibration Quality - Chong, Sook-Yee; Dorow, Beate; Ramasamy, Ellankavi; Dennerlein, Florian; Röhrle, Oliver (Frontiers in Bioengineering and Biotechnology, 2015)
Optical motion capture systems are widely used in sports and medicine. The performance of these systems depends on, amongst other factors, the quality of the camera calibration process. This study proposes a technique to assess the accuracy of the extrinsic camera parameters, as estimated during calibration. This method relies on the fact that solid objects in the real world cannot possess a gap in between, nor interpenetrate, when in contact with each other. In our study, we used motion capture to track successive collisions of two solid moving objects. The motion of solid objects was simulated based on trajectories measured by a multi-camera system, and geometric information acquired from computed tomography. The simulations were then used to determine the amount of overlap or gap between them. This technique also takes into account errors resulting from markers moving close to one another, and better replicates actual movements during motion capture. We propose that this technique of successively colliding two solid moving objects may provide a means of measuring calibration accuracy.